The Problem of friendship in ethics - Mira Bohórquez, Paula Cristina (Estudios de Filosofía, 2010)
This paper analyzes the reactivation of the question of the importance of friendship for Ethics. In a first part it analyzes, from diverse perspectives, the criticisms, which become stronger as time goes by, to the impartiality and universalist theories of Ethics, that have raised in turn the rebirth of the treatment of friendship as a moral phenomenon; such analysis pretends to call the attention on diverse critical points of the so-called Theories of Friendship. In a second part is analyzed the Aristotelian model of virtuose friendship, showing the structure of this kind of friendship and its relationship to Ethics, to stress thus some points of the Aristotelian Theory of Friendship that can be helpful for a better understanding of the problem nowadays.